Enhancing the Accessibility of Technical Education in Indonesia: The Role of Cloud-Based Remote Laboratories in Rural and Disadvantaged Areas - Effendi, Dwi Erlin; Sterzer, Sebastián (Generate Digital Publishing, 2024)
ABSTRACT Objective: This study aims to explore the application of cloud-based remote laboratories in engineering education, particularly in addressing educational disparities in remote and underdeveloped areas of Indonesia. Research Design & Methods: This research method uses a comprehensive literature review approach conducted in conjunction with the analysis of sample applications to assess the potential of cloud-based distance laboratories. This research focuses on accessibility, learning effectiveness, scalability, and cost efficiency, taking into account the role of government and collaboration between stakeholders. Findings: The findings reveal that cloud-based remote laboratories can significantly enhance the technical quality of engineering education in Indonesia by overcoming geographic, temporal, and financial barriers. However, challenges such as limited internet access and high initial infrastructure costs remain key obstacles. Implications & Recommendations: To ensure successful implementation, the study emphasizes the need for government investment in ICT infrastructure, fostering partnerships between the private sector and educational institutions, and developing strategic policies to mitigate implementation challenges. Contribution & Value Added: This study contributes to the discourse on leveraging ICT to bridge educational gaps in developing countries. It highlights cloud-based remote laboratories as a transformative solution for advancing engineering education, promoting equity, and enhancing Indonesia's competitiveness in the global technology and industrial sectors.